The electromagnet, and electromagnetic mechanism - Thompson, Silvanus (University of California Libraries, 1891)
Silvanus P. Thompson (18511916) was an engineer and physicist who researched aspects of electricity, magnets and optics. He spent his career teaching, first as a professor in Bristol and later in London, at the City and Guilds Finsbury Technical College, and he was a frequent public speaker on scientific matters. Over the course of his career he became especially interested in technical education, and produced many books that explained complicated scientific concepts with clarity, including his most famous work Calculus Made Easy. In this work, published in 1891, Thompson explains the importance and function of the electromagnet. Starting with the history and development of electromagnets, the work looks at the principle of the magnetic current, and gives detailed descriptions including numerous technical illustrations of electromagnetic motors and machine tools, providing an engaging guide to the latest forms of scientific knowledge at the end of the nineteenth century.